Balanced Scorecard as A Performance Measurement Instrument for The Obi District Government, South Halmahera Regency - Naswan Hadilia; Aspiati A. Samiun (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
This study aims to measure the performance of Obi District, South Halmahera Regency, using the Balanced Scorecard method. The Balanced Scorecard is a performance measurement method that is able to provide a comprehensive picture of organizational performance, both from financial and non-financial aspects. The results of the study indicate that financial performance measured through a budget perspective with an effectiveness ratio has increased. In 2022 the effectiveness ratio reached 95.5% and was included in the effective category, in 2023 it increased to 97.2% with an effective category, and in 2024 it reached 98.8% which was also in the effective category. Meanwhile, measurements through the efficiency ratio showed that in 2022 the efficiency value was 28.2% and was included in the very efficient category, in 2023 it was 26.8% in the very satisfactory category, and in 2024 it was 25.5% which was also in the very satisfactory category. Non-financial performance shows that from a customer perspective, the average overall score reached 80% which was included in the satisfactory category. The internal business process perspective also achieved an average score of 75%, indicating a satisfactory rating. Meanwhile, the growth and learning perspective achieved an average score of 69%, remaining in the satisfactory rating.